Nerve growth factor is expressed and stored in central neurons of adult zebrafish. Issue 1 (4th April 2019) - Cacialli, Pietro; Gatta, Claudia; D'Angelo, Livia; Leggieri, Adele; Palladino, Antonio; de Girolamo, Paolo; Pellegrini, Elisabeth; Lucini, Carla
Abstract : Nerve growth factor (NGF), a member of the neurotrophin family, was initially described as neuronal survival and growth factor, but successively has emerged as an active mediator in many essential functions in the central nervous system of mammals. NGF is synthesized as a precursor pro‐NGF and is cleaved intracellularly into mature NGF. However, recent evidence demonstrates that pro‐NGF is not a simple inactive precursor, but is also secreted outside the cells and can exert multiple roles. Despite the vast literature present in mammals, studies devoted to NGF in the brain of other vertebrate models are scarce. Zebrafish is a teleost fish widely known for developmental genetic studies and is well established as model for translational neuroscience research. Genomic organization of zebrafish and mouse NGF is highly similar, and zebrafish NGF protein has been reported in mature and two‐precursors forms. To add further knowledge on neurotrophic factors in vertebrate brain models, we decided to determine the NGF mRNA and protein distribution in the adult zebrafish brain and to characterize the phenotype of NGF‐positive cells. NGF mRNA was visualized by in situ hybridization on whole‐mount brains. NGF protein distribution was assessed on microtomic sections by using an antiserum against NGF, able to recognize pro‐NGF in adult zebrafish brain as demonstrated also in previous studies. To characterize NGF‐positive cells, anti‐NGF was employed on microtomic slides of aromatase B transgenic zebrafish (where radial glial cells appeared fluorescent) and by means of double‐immunolabeling against NGF/proliferative cell nuclear antigen (PCNA; proliferation marker) and NGF/microtube‐associated protein2 (MAP2; neuronal marker). NGF mRNA and protein were widely distributed in the brain of adult zebrafish, and their pattern of distribution of positive perikaryal was overlapping, both in males and females, with few slight differences. Specifically, the immunoreactivity to the protein was observed in fibers over the entire encephalon. MAP2 immunoreactivity was present in the majority of NGF‐positive cells, throughout the zebrafish brain. PCNA and aromatase B cells were not positive to NGF, but they were closely intermingled with NGF cells. In conclusion, our study demonstrated that mature neurons in the zebrafish brain express NGF mRNA and store pro‐NGF. Abstract : NGF mRNA and proNGF protein were widely distributed in the brain of adult zebrafish. The pattern of distribution of positive perikarya was overlapping, both in males and females, with few slight differences. The co‐presence of pro‐NGF and the neuronal marker MAP2 immunoreactivity throughout the brain of adult zebrafish demonstrates that pro‐NGF containing cells are neurons.